Effect of Acacia nilotica Litter on its Biomass and Properties of a Sodic Soil - Singh, Harinder; Singh, Gurbachan (Indian Journal of Agroforestry, 2020)
A pot experiment was conducted from May to November, 1994 at Central Soil Salinity Research Institute, Karnal (Haryana) to study the effect of Acacia nilotica litter levels (0, 1:4 and 1:2, litter: soil on volume basis) on its saplings and on the properties of sodic soil. The mean height and girth growth attained by Acacia saplings was maximum in no litter treatment and minimum when litter was added in 1:2; similarly biomass accumulated in leaf, stem and root of Acacia was almost half when litter was added 1:2 ratio than control. Acacia plant had better P and Zn content when these were grown in litter treated soil. There was appreciable decrease in pH and improvement in organic carbon, available P and K content of soil with litter addition; highest effect being when litter was added in 1:2 ratio.